Emergence and Evolution of ERM Proteins and Merlin in Metazoans - Shabardina, Victoria (Genome Biol Evol, 2019)
Ezrin, radixin, moesin, and merlin are cytoskeletal proteins, whose functions are specific to metazoans. They participate in cell cortex rearrangement, including cell–cell contact formation, and play an important role in cancer progression. Here, we have performed a comprehensive phylogenetic analysis of the proteins spanning 87 species. The results describe a possible mechanism for the protein family origin in the root of Metazoa, paralogs diversification in vertebrates, and acquisition of novel functions, including tumor suppression. In addition, a merlin paralog, present in most vertebrates but lost in mammals, has been described here for the first time. We have also highlighted a set of amino acid variations within the conserved motifs as the candidates for determining physiological differences between ERM paralogs.